2000
DOI: 10.1002/(sici)1521-4141(200004)30:4<1162::aid-immu1162>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal antibody screening of a phage-displayed random peptide library reveals mimotopes of chemokine receptor CCR5: implications for the tertiary structure of the receptor and for an N-terminal binding site for HIV-1 gp120

Abstract: The chemokine receptor CCR5 contains seven transmembrane‐spanning domains. It binds chemokines and acts as co‐receptor for macrophage (m)‐tropic (or R5) strains of HIV‐1. Monoclonal antibodies (mAb) to CCR5, 3A9 and 5C7, were used for biopanning a nonapeptide cysteine (C)‐constrained phage‐displayed random peptide library to ascertain contact residues and define tertiary structures of possible epitopes on CCR5. Reactivity of antibodies with phagotopes was established by enzyme‐linked immunosorbent assay (ELISA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 47 publications
3
19
0
Order By: Relevance
“…3A9 has been demonstrated to bind to a conformational epitope of CCR5 that includes the EC1 domain (29). Whole blood from a naïve pig-tailed macaque was incubated with a MAb against CD95 along with IgG from either a vaccinated (97P026) or a control (96P080) macaque and then reacted with a limiting amount of PE-labeled 3A9.…”
Section: Resultsmentioning
confidence: 99%
“…3A9 has been demonstrated to bind to a conformational epitope of CCR5 that includes the EC1 domain (29). Whole blood from a naïve pig-tailed macaque was incubated with a MAb against CD95 along with IgG from either a vaccinated (97P026) or a control (96P080) macaque and then reacted with a limiting amount of PE-labeled 3A9.…”
Section: Resultsmentioning
confidence: 99%
“…In initial flow cytometric experiments, human PBMCs were gated for expression of both CD3 and CD4 or CD8 and were stained with 3 monoclonal anti-CCR5 antibodies recognizing different domains. [14][15][16][17] In agreement with the findings of Achour et al, 11 we found that, although cells from each donor indicated variable but universally low levels of CCR5 staining on nonpermeabilized cells, uniformly strong signals were obtained on fixed and permeabilized cells ( Figure 1A). Control GHOST (3) parental cell lines that do not express CCR5, however, also gave positive results when the same anti-CCR5 antibodies were used to stain fixed and permeabilized cells ( Figure 1B).…”
mentioning
confidence: 99%
“…1C) (3). Interestingly, some peptide sequences contained additional amino acid motifs present in extracellular loops 1 and 3 of CCR5, which were previously described to be present in the mimotopes that we selected with two HIV-neutralizing MAbs against CCR5 (MAbs 3A9 and 5C7) and to be involved in HIV-1 entry (33,34,42). Due to its high reactivity, frequent selection, and strong sequence similarity to different extracellular regions of coreceptors, phage a was further analyzed.…”
Section: Resultsmentioning
confidence: 99%